Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1029/2009wr007814
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing input and structural uncertainty of nonlinear dynamic models with stochastic, time‐dependent parameters

Abstract: [1] A recently developed technique for identifying continuous-time, time-dependent, stochastic model parameters is embedded in a general framework for identifying causes of bias and reducing bias in dynamic models. In contrast to the usual approach of considering bias in model output with an autoregressive error model or a stochastic process, we make the attempt to correct for bias within the model or even in model input. This increases the potential of learning about the causes of bias and of subsequently cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
198
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(202 citation statements)
references
References 60 publications
2
198
0
1
Order By: Relevance
“…The most popular method to date is probably Bayesian multimodel averaging (BMA) [Hoeting et al, 1999;Neuman, 2003aNeuman, , 2003b, which uses multiple structures to characterize the uncertainty in our knowledge of the mechanics of underlying hydrological processes Georgakakos et al, 2004;Ajami et al, 2006;Duan et al, 2007]. Other methods seek not just to characterize model structure uncertainty but to also improve the structure of the hydrological model; examples include time-variable parameter methods such as the state-dependent parameter (SDP) estimation method [Young et al, 2001;Young and Ratto, 2009], the recursive prediction error (RPE) approach [Lin and Beck, 2007], and the time-dependent parameters approach [Reichert and Mieleitner, 2009]. Recently, a new method called the Bayesian estimation of structure (BESt) approach [Bulygina and Gupta, 2009 has been proposed to resolve the underlying structure of the model via data assimilation conducted on the raw data.…”
Section: Introductionmentioning
confidence: 99%
“…The most popular method to date is probably Bayesian multimodel averaging (BMA) [Hoeting et al, 1999;Neuman, 2003aNeuman, , 2003b, which uses multiple structures to characterize the uncertainty in our knowledge of the mechanics of underlying hydrological processes Georgakakos et al, 2004;Ajami et al, 2006;Duan et al, 2007]. Other methods seek not just to characterize model structure uncertainty but to also improve the structure of the hydrological model; examples include time-variable parameter methods such as the state-dependent parameter (SDP) estimation method [Young et al, 2001;Young and Ratto, 2009], the recursive prediction error (RPE) approach [Lin and Beck, 2007], and the time-dependent parameters approach [Reichert and Mieleitner, 2009]. Recently, a new method called the Bayesian estimation of structure (BESt) approach [Bulygina and Gupta, 2009 has been proposed to resolve the underlying structure of the model via data assimilation conducted on the raw data.…”
Section: Introductionmentioning
confidence: 99%
“…Abramowitz et al [2006] model systematic deviations between the model simulations and observed data; Kuczera et al [2006] and Reichert and Mieleitner [2009] treat parameters as stochastic variables with possible time or state dependency; Kennedy and O'Hagan [2001] stochastically estimate the model equations themselves when all model inputs, states, and outputs are observable.…”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies, such as the study of Reichert and Mieleitner [33], have analyzed the input uncertainty of lumped conceptual nonlinear models by observing the variation of rainfall input multipliers for optimal results; however, by using the distributed hydrological models, such as the DYRIM in this study, the uncertainty quantization of rainfall input would be more complicated and difficult. In this study, we focus on the change of uncertainty corresponding to the number of rainfall stations.…”
Section: Uncertainty Quantization Of Basin Rainfall and Simulated Runoffmentioning
confidence: 95%
“…To alleviate the influence of rainfall spatial uncertainty, Blume et al [32] proposed an event-based runoff coefficient in combination with simple statistical models that could improve the understanding of the rainfall-runoff response of catchments with sparse data. Reichert and Mieleitner [33] proposed a time-dependent rainfall multiplier at the input side of a hydrological model, which was adjusted according to the goodness of fit of model results.…”
Section: Introductionmentioning
confidence: 99%